Proceedings of the Twenty-Eighth International Joint Conference on Artificial Intelligence 2019
DOI: 10.24963/ijcai.2019/523
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Multi-Purpose Sessions for Next-Item Recommendations via Mixture-Channel Purpose Routing Networks

Abstract: A session-based recommender system (SBRS) suggests the next item by modeling the dependencies between items in a session. Most of existing SBRSs assume the items inside a session are associated with one (implicit) purpose. However, this may not always be true in reality, and a session may often consist of multiple subsets of items for different purposes (e.g., breakfast and decoration). Specifically, items (e.g., bread and milk) in a subsethave strong purpose-specific dependencies whereas items (e.g., bread an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(52 citation statements)
references
References 16 publications
0
52
0
Order By: Relevance
“…• NARM: An RNN-based model that applies an attention mechanism to capture users' main purposes from the hidden states and combines it with sequential behavior as final representations of users' current preferences [24], which shares a similar spirits as IDSR when calculating the relevance scores for items. • MCPRN: The most recently proposed method that models users' multiple purposes in a session [42]. The authors claim that they can improve the performance over the state-of-the-art methods in terms of both accuracy and diversity.…”
Section: Methods Used For Comparisonmentioning
confidence: 99%
See 1 more Smart Citation
“…• NARM: An RNN-based model that applies an attention mechanism to capture users' main purposes from the hidden states and combines it with sequential behavior as final representations of users' current preferences [24], which shares a similar spirits as IDSR when calculating the relevance scores for items. • MCPRN: The most recently proposed method that models users' multiple purposes in a session [42]. The authors claim that they can improve the performance over the state-of-the-art methods in terms of both accuracy and diversity.…”
Section: Methods Used For Comparisonmentioning
confidence: 99%
“…The studies mentioned above ignore the fact that users might have multiple intents reflected in their sequential behavior. Wang et al [42] have proposed a mixture-channel purpose routing networks (MCPRNs) to capture users' different intents in a given session. MCPRN first applies a purpose routing network to detect multiple purposes of a user and then models the items with a mixture-channel RNN, where each channel RNN models the item dependencies for a specific purpose.…”
Section: Sequential Recommendationmentioning
confidence: 99%
“…In another study [48], some regularization terms are proposed to be added to the RankALS and RankSGD approaches to generate a more diverse recommendation list. Wang et al [49] proposed the mixture-channel purpose routing networks (MCPRNs) that can cover multiple purposes of the user in the session by recommending a more diverse recommendation list. They showed that their model has better accuracy and diversity compared to the baselines.…”
Section: Diversity Modelingmentioning
confidence: 99%
“…Having known the partial differential of the chain rule, we can update the weight matrix W and algorithm latent matrix V by the following updating rule Eqs. (20) and (21) , where η is the learning rate.…”
Section: A32 Updating Rulementioning
confidence: 99%
“…When applying RS approaches in the AS problems, we need to note that the recorded algorithms' performances on problem instances are usually in much smaller size. Thence the state-of-the-art deep learning and transaction embedding techniques in the large-scale session-based RS [19,20] are not suitable for AS scenarios. On the contrary, shallow ML approaches from RS are more adaptable.…”
Section: Introductionmentioning
confidence: 99%